2016
DOI: 10.1016/j.amepre.2015.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Older Adult Falls Seen by Emergency Medical Service Providers

Abstract: Introduction Among people aged ≥65 years, falling is the leading cause of emergency department visits. Emergency medical services (EMS) are often called to help older adults who have fallen, with some requiring hospital transport. Chief aims were to determine where falls occurred and the circumstances under which patients were transported by EMS, and to identify future fall prevention opportunities. Methods In 2012, a total of 42 states contributed ambulatory data to the National EMS Information System, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
36
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 25 publications
3
36
0
3
Order By: Relevance
“…Ours is one of the few tests of an EMT-delivered, at-scene, public-health-oriented outreach intervention to prevent future falls among elder community-dwelling 9-1-1 callers. The frequency of 9-1-1 calls for falls in our study (12–16%) was very consistent with national data showing that among adults aged 65+, calls for falls account for 17% of all EMS calls (12). Older adults who have fallen and called 9-1-1 are at very high risk for recurrent falls (13) and serious injury or death.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Ours is one of the few tests of an EMT-delivered, at-scene, public-health-oriented outreach intervention to prevent future falls among elder community-dwelling 9-1-1 callers. The frequency of 9-1-1 calls for falls in our study (12–16%) was very consistent with national data showing that among adults aged 65+, calls for falls account for 17% of all EMS calls (12). Older adults who have fallen and called 9-1-1 are at very high risk for recurrent falls (13) and serious injury or death.…”
Section: Discussionsupporting
confidence: 91%
“…Prior research has noted the EMS providers are in an opportune position to provide fall-risk-reduction interventions and/or referrals to community programs and services (12). Ours is one of the few tests of an EMT-delivered, at-scene, public-health-oriented outreach intervention to prevent future falls among elder community-dwelling 9-1-1 callers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher rate of repeat transport for males was observed in the multivariable model, but the association was small. The higher rate of repeat transports for older adults in health or residential institutions compared to home dwelling older adults is also consistent with prior work, 36 and suggests this population as a potential target for interventions. Our data do not include patient characteristics such as comorbidities and functional status that likely at least partially explain the observed association between living in a residential institution and repeat EMS transports.…”
Section: Discussionsupporting
confidence: 85%
“…One person called 75 times over the study period. Previous work demonstrated that 80% of fall calls to 911 resulted in transport for further care . The current study demonstrated that there is a dramatic shift in transport to care, with individuals who call more frequently having an 80% chance of no need for transport to care.…”
Section: Discussionmentioning
confidence: 99%